(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research is concerned with the lack of cooperation skills of students, so the effect on the learning process, especially when the implementation group discussion.This research is being conducted in Class XI Unggulan SMA Pasundan 8 Bandung. The main purpose of this research is to improve the cooperation skills of students in learning history. The indicator to measure cooperation skills in this research is to using the agreement, organizing, being in groups, and taking turns and sharing assignments. This reseach uses the classroom action research designed by Kemmis and Mc Taggart which consists of four stages: planning, acts, observation and reflection. This research was conducted in three cycles. According to the data that has been analysed, there’s an increase on every cycle in the students developments to reach the criteria of cooperation skills indicator, this can be seen by looking at the scores on every indicator in each cycle. This shows success at the applying in the method Quick On The Draw in improving the cooperation skill of students.